Becoming InterActive for Life: Mobilizing Relational Knowledge for Physical Educators - Lloyd, Rebecca J.; Smith, Stephen J. (Frontiers in Sports and Active Living, 2022)
The overarching purpose of the InterActive for Life (IA4L) project is to mobilize relational knowledge of partnered movement practices for physical education practitioners. Through a participatory, motion-sensing phenomenological methodology, relational knowledge gleaned from world class experts in salsa dance, equestrian arts, push hands Tai Chi and acroyoga, and analyzed through the Function2Flow conceptual model, was shared with Physical Education Teacher Education (PETE) students. They, in turn, made sense of the ways these experts cultivate relational connections through a process of designing interactive games suitable for physical education curricula. The kinetic, kinesthetic, affective and energetic dynamics of these games were then shared through professional development workshops, mentoring, and open-access resources. Each phase of the IA4L project invites us to depart from the predominance of individualistic ways of conceiving and teaching movement and instead explore what it means to be attuned to the pulse of life as we break away from tendencies to objectify movement as something our bodies do or that is done to them. Consideration is given to the ways in which meaningful relational connections are formed in and through movement and how this learning prioritizes the InterActive Functions, Forms, Feelings and Flows of moving purposefully, playfully and expressively with others. In so doing, what this research offers is an understanding of how knowledge of an essentially motion-sensitive kind, which can breathe life into physical education curricula, can be actively and interactively mobilized.